hsa_circ_0111707 Is Associated With Risk of Stress-Related Type 2 Diabetes via Sponging miR-144-3p - Yan, Yu-Xiang; Xiao, Huan-Bo; Lu, Ya-Ke; Sun, Yue; Wang, Shuo; Dong, Jing; Wu, Li-Juan (Frontiers in Endocrinology, 2022)
Introduction: Chronic stress plays an important role in the development of type 2 diabetes (T2D). circular RNAs (circRNAs) play significant roles in regulating the pathogenesis of diseases by regulating gene expression. The aim of the present study was to identify the association between hsa_circ_0111707 and stress-related T2D. Methods: The present study was performed based on a three-parts design. The association between hsa_circ_0111707 in peripheral blood mononuclear cells (PBMCs) and T2D and stress-related variables were assessed in a cross-sectional study. The causal relationship of hsa_circ_0111707 on T2D was further investigated in a nested case-control study. miR-144-3p as the miRNA target of hsa_circ_0111707 was verified by dual-luciferase reporter assay and RNA immunoprecipitation (RIP) assay. Results: The relative expression of hsa_circ_0111707 was significantly lower in the T2D and impaired fasting glucose (IFG) cases in comparison to controls. The hsa_circ_0111707 expression was significantly negatively correlated with miR-144-3p expression and plasma cortisol concentration, and positively correlated with NR3C1 expression. In addition, hsa_circ_0111707 expression was negatively correlated with scores of “demands at work” and “insecurity at work” of Copenhagen Psychosocial Questionnaire (COPSOQ). Decreased hsa_circ_0111707 expression was associated with increased risk of T2D development. Functional analysis demonstrated that hsa_circ_0111707 functions as a sponge for miR-144-3p. Conclusion: hsa_circ_0111707 is associated with risk of T2D development via sponging miR-144-3p. hsa_circ_0111707 in PBMCs can be considered as a potential marker of stress-related T2D.